Influence of bile acid derivates on morphine analgesic effect in mice - Vasović, Velibor; Vukmirović, Saša; Mikov, Momir; Mikov, Ivan; Budakov, Zorana; Stilinović, Nebojša; Milijašević, Boris (Vojnosanitetski pregled, 2014)
Background/Aim. It is known that bile acids improve the absorption, bioavailability and pharmacodynamic characteristics of some drugs. Morphine analgesia is produced by activation of opioid receptors within the central nervous system (CNS) at both spinal and supraspinal levels. Since a morphine molecule contains 3 polar groups and therefore hard to transfer through the blood-brain barrier, the aim of the study was to examine the potential influence of bile acids derivates, namely sodium salt of monoketocholic acid (MKH-Na) and methyl ester of monoketocholic acid (MKH-Me), on analgesic effect of morphine. Methods. White male mice of NMRI-Haan strain, with body weight of 20–24 g, were used in this study. The analgesic effect of morphine (administered by subcutaneous and intramuscular route in a dose of 2 mg/kg), with and without pretreatment with MKH-Na (4 mg/kg) and MKH-Me (4 mg/kg) was estimated by the hot plate method. Results. Administration of MKH-Me prior to subcutaneous administration of morphine increased the morphine analgesic effect but the increase was not statistically significant. At the same time administration of MKH-Na did not affect morphine analgesic effect. The analgesic effect of morphine increased when administered intramuscularly 20 min after MKH-Me administration. When compared with the group of animals treated only with morphine, a statistically significant increase in analgesic effect was detected 10, 30, 40 and 50 min after morphine administration (p < 0.05). Pretreatment with MKH-Na did not affect morphine analgesic effect. Conclusion. According to the results of this study it can be presumed that after intramuscular morphine administration methyl ester of monoketocholic acid increases morphine transport into the central nervous system and consequently the analgesic effect, as well. Further research on bile acids-morphine interaction both in vitro and in vivo is necessary to completely elucidate the mechanism of this interaction and increase in the morphine analgesic effect.
Keywords: morphine; mice; bile acids and salts; blood-brain barrier